ANALISIS FAKTOR – FAKTOR YANG MEMENGARUHI MANAJEMEN PAJAK PERUSAHAAN - Albertus, Wenny; Susanty, Meinie (E-Jurnal Akuntansi TSM, 2024)
The purpose of this study is to obtain empirical evidence regarding the influence of company size, independent commissioners, management compensation, profitability, leverage, and capital intensity ratio on tax management. The data used in this research are consumer cyclical and non-cyclical companies that are consistently listed on the Indonesia Stock Exchange (BEI) for three years from 2020 to 2022. Purposive sampling method is used in this research with total sample of 64 companies or 192 years of data. The data obtained from the samples were analyzed using multiple regression methods. The results of this research show that the variables company size, profitability, and leverage have an influence on tax management, while independent commissioners, management compensation, and capital intensity ratios have no influence on tax management.